Edge-Etched Al2O3 Dielectric as Charge Storage Region in a Coupled MIS Tunnel Diode Sensor - Bo-Jyun Chen; Jenn-Gwo Hwu (IEEE Journal of the Electron Devices Society, 2020)
The effects of an Al2O3 dielectric patterned by wet etching in a metal-insulator-semiconductor (MIS) tunnel diode are studied by I-V, C-V and charge storage characteristics in this paper. The behaviors are obviously different from the device without an etched edge. It is suggested that traps are formed at the edge because of the etching process. A circuit model is proposed to explain the effect of the existence of additional traps. With the etched edge as charge storage region, current ratio of programmed and erased states of the tunnel diode sensor is expanded for 165 times and the retention characteristic is much improved. Meanwhile, charge storage characteristic varies with the thickness of the Al2O3 dielectric. Multilevel demonstration is carried out by specified programming process which is not feasible on coupled MIS previously. In addition, relation between the sensing current and stress conditions is examined. A maximum on/off ratio of 105 is achieved. The study of the etched edge is believed to be beneficial for future development in memory cell constructed by MIS TD.